Kantasaamen *-(e̮)hče̮-frekventatiivijohtimen edustuksesta nykyisissä saamelaiskielissä - Koponen, E. (Eino); Kuokkala, J. (Juha) (2021)
Abstract A survey of Saami *-(e̮)hče̮ frequentative verbs is made based on dictionary data from all Saami languages. The analysis of their base verbs shows that in most of the languages, the frequentative derivatives are not restricted to *ē-stem bases as in North Saami; specifically in Skolt and Kildin Saami, the derivational type seems to be productive on *e̮- and *ō-stems as well.